Public Intervention in The Formal Housing Market in Indonesia: Who Gets The Benefits - Winarso, Haryo; Kombaitan, B. (Journal of Regional and City Planning, 2004)
Alongside the economic boom experienced in Indonesia during the 1980s and the early 1990s, a remarkable land development for residential purposes has taken place. In Jakarta and its surrounding areas, for instances, the formal private developers were able to sell an average of more than twenty five thousand housing units annually and to transform 16.6 thousand hectares of land into residential areas within 20 years alone. However, due ti the unsound loan management this massive land development is believed to be one of the factors triggering economic crisis in Indonesia. For almost four years now the government intervenes with a measure attempting to recover the housing market that has been collapse since the economic crisis hit in 1997. The government set up an ad hoc institution and bailed out most of the debt created by the excessive of the government intervention in the housing market. The paper argues that the government intervention has never been effective particularly because the socio-political and economic condition of the country is still uncertain. In this circumstance the intervention benefits only small minority developers and ignoring the large majority of low-income potential buyers.Keywords: formal housing market, public intervention, perumnas